Do not attempt cardiopulmonary resuscitation (DNACPR) decisions for older medical inpatients: a cohort study - Walker, J; Burke, K; Wanat, M; Hobbs, H; Rocroi, I; Sharpe, M (BMJ Publishing Group, 2021)
Objectives: A decision not to attempt cardiopulmonary resuscitation in the event of cardiorespiratory arrest requires a discussion between the doctor and the patient and/or their relatives. We aimed to determine how many older patients admitted to acute medical wards had a pre-existing 'do not attempt cardiopulmonary resuscitation' (DNACPR) decision, how many had one recorded on the ward and how many of those who died had a DNACPR decision in place. Methods: A prospective cohort study, using data from medical records, of 481 consecutive patients aged ≥65 years admitted to the six acute medical wards of the John Radcliffe Hospital, Oxford. Results: 105/481 (22%) had a DNACPR decision at ward admission, 30 of which had been made in the emergency unit. A further 45 decisions were recorded on the ward, mostly after discussion with relatives. Of the 37 patients who died, 36 had a DNACPR decision. For the 20 deceased patients whose DNACPR decision was recorded during their admission, the median time from documentation to death was 4 days with 7/20 (35%) recorded the day before death. Conclusions: Older patients with multimorbidity need the opportunity to discuss the role of CPR earlier in their care and preferably before acute hospital admission.